Effectiveness of vaginal analgesic electrostimulation versus sacral electroacupuncture in chronic pelvic pain of myofascial origin - Ochoa, Cristóbal B.; Reyes, Guadalupe G.; M. Marin, Claudia Monserrat; A. Quispe, Vianey Brigida; Gonzalez, Adrian G.; Velázquez, Ricardo H.; Guerrero, Alejandra Aguirre (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Chronic pelvic pain (CPP) of myofascial origin is a condition that is difficult to control and with great repercussion on the quality of life for women who suffer from it. This study objective was to compare the effectiveness of two treatments for the management of this pathology; vaginal analgesic electrostimulation (VES) versus sacral electroacupuncture (EAS). Methods: Quasi-experimental comparative study of two treatments in patients with myofascial CPP. The sample was made up of women who presented this condition during the period 2016 to 2019. The main objective was to assess the effectiveness of the treatments in comparison in terms of the decrease in the VAS score, the secondary ones were: To know the effectiveness of the VES for pain chronic pelvic myofascial (MFPP), the effectiveness of EA for the same condition, complications of therapies, main urological dysfunctions and other chronic pelvic pain associated with myofascial CPP. Results: Thirteen thousand patient files were reviewed, of which 47 were diagnosed with myofascial CCP, with 38 patients eligible for our study. The VES was more effective than the EAS in decreasing the VAS in the twelfth session from 1.36 versus 2.62 p .001. Both therapies were effective for the management of myofascial DCP as they decreased the VAS score to more than 60% of the initial VAS. Vulvodynia (34%), mixed urinary incontinence (32%), and voiding symptoms (26%) were other pelvic floor dysfunctions that presented concomitantly to the MFPP. Conclusions: In patients with myofascial CPP, vaginal VES is better than AD for the treatment of this condition.